2021
DOI: 10.1016/j.sjbs.2021.03.079
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nutritional quality and volatile flavor compounds among bighead carp from three aquaculture systems

Abstract: To explore the differences in the nutritional quality of the muscles of bighead carp from different environments and aquaculture systems, we investigated three types of water bodies typically used for aquaculture: A common culture pond (NC), a natural lake (PY), and a cold water reservoir (XHK). Parameters affecting quality were evaluated, including muscle microstructure, fatty acid profiles, amino acid profiles, and volatile compounds. Fish from the XHK reservoir had the smallest muscle fiber diameter and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…Our previous study [ 12 ] showed significant differences in bighead carp muscle fatty acids, amino acids, and volatile flavour compounds in different aquaculture systems, suggesting that the culture systems could affect muscle quality. However, the potential relationship between the culture systems and muscle quality needs further exploration [ 12 ], where gut microbes may play a crucial role. Studies have reported the impact of gut microbiota on muscle quality in other species [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study [ 12 ] showed significant differences in bighead carp muscle fatty acids, amino acids, and volatile flavour compounds in different aquaculture systems, suggesting that the culture systems could affect muscle quality. However, the potential relationship between the culture systems and muscle quality needs further exploration [ 12 ], where gut microbes may play a crucial role. Studies have reported the impact of gut microbiota on muscle quality in other species [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the nutritional value and sensory traits of fish muscle are affected by the culture environment [ 14 , 15 ]. In bighead carp ( Hypophthalmichthys nobilis ), due to the presence of abundant volatiles with distinct aromas, fish cultured in cold water reservoirs and common culture ponds developed a greater umami intensity than those captured from a natural lake [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In China, based on data provided by the Bureau of Fisheries, Ministry of Agriculture and Rural Affairs of the PRC, the total fish production in China was 35.30 million tons in 2019, with a per capita of 25.30 kg. However, the nutritional composition has only been evaluated in a few fish species in China, such as pomfret ( Pampus punctatissimus ) (Zhao et al., 2010), pufferfish ( Fugu obscurus , Fugu flavidus , and Fugu rubripes ) (Tao et al., 2012), common carp ( Cyprinus carpio ) (Cai et al., 2021), and bighead carp ( Aristichthys nobilis ) (Hu et al., 2021). The nutritional value of most market fish has not been objectively evaluated, and consumers can only judge the quality of fish according to their price and be generally misled to believe that the higher the price, the better the quality.…”
Section: Introductionmentioning
confidence: 99%